Correlation between the Compressive, Tensile Strength of Old Concrete under Marine Environment and Prediction of Long-Term Strength - Weilai Yao; Shiyong Jiang; Wei Fei; Tao Cai (Advances in Materials Science and Engineering)
Compressive strength and tensile strength are important mechanical properties of concrete. The long-term strength of concrete under real service environment is an important parameter when evaluating existing buildings, which should also be properly considered in structural design. In this study, the relationship between compressive and splitting tensile strength of old concrete existing for long period under marine environment was investigated. At a deserted harbour, concrete cores samples were drilled by pairs in site. For each pair of samples, the two cores were drilled from the adjacent location and conducted to compressive, splitting tensile test, respectively. 48 compressive and splitting tensile strengths were finally obtained. From the test results, tensile strength presents general uptrend with compressive strength, and the two parameters are well positively correlated. Exponential model generally recommended by building codes or literatures is still capable of describing the relationship between compressive and tensile strength of old deteriorated concrete, when function parameters are properly determined. Based on statistical theory and the experimental result of this study, a method for predicting long-term tensile strength of concrete is developed and an example is given, which may provide a potential way to estimate long-term concrete strength under real marine environment.